Study on Acceptable Noise Standards for Motorcycles, in Accordance with the Ecuadorian Technical Regulation INEN 136 (1R), Assessed through Dynamic and Static Tests - Puente Moromenacho, Edwin; Moreno Guamán, Gladys Yolanda; Noroña Merchán, Marco Vinicio; Cruz Mangui, Mayra Cecilia (INGENIO, 2024)
In the year 2020 Ecuador and the whole world was affected by the biggest health crisis in recent times. Covid 19 forced many Ecuadorians to look for new sources of income, and they found the possibility of doing so in motorcycles, since deliveries were a modality that many businesses adapted. This increase in motorcycles brings with it an increase in noise pollution. That makes us question ourselves of whether in this growth outside the trend that the sale of motorcycles had, the standards and maximum noise limits that motorcycles are allowed to produce to be able to circulate in our country continued to be complied with. For this, we adopted the role of an accredited laboratory and carried out the static and dynamic tests, following the procedures of the European Directive 78/1015/CEE, on a sample of five motorcycles to verify whether or not they complied with the INEN RTE 136 Motorcycles standard, which It is where the maximum values that can be emitted by displacement category are exposed. With the results obtained we were able to conclude and make certain recommendations.